Neverwhere : the author's preferred text - Gaiman, Neil; Gaiman, Neil (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2017)
An author-preferred edition of the story of Richard Mayhew, who discovers an alternate city beneath London, reconciles inconsistencies between the U.S. and U.K. versions, reinstates previously cut scenes, and incorporates the Neverwhere tale "How the Marquis Got His Coat Back."
Includes the short story How the marquis got his coat back.
Keywords: Underground homeless persons -- Fiction; Underground areas -- Fiction; Businessmen -- Fiction; Subways -- Fiction; Homeless persons -- Fiction; Businessmen -- Fiction; Subways -- Fiction; London (England) -- Fiction; London (England) -- Fiction; Fantasy fiction; Horror fiction; Fantasy fiction; Horror fiction